Behavioral and psychological symptoms in dementia is not a unitary concept: A critical review with emphasis on Alzheimer's disease - Laks, Jerson; Engelhardt, Eliasz (Dementia & neuropsychologia, 2008)
Abstract Behavioral and Psychological Symptoms of Dementia (BPSD) is an important feature of dementia. However, this definition comprises a large array of symptoms and syndromes. This hampers understanding of the behavior of patients with dementia and the devising of strategies to ameliorate these symptoms. Objectives: This review aimed to describe the main factors and syndromes that comprise BPSD, as well as neuroimaging, psychopharmacological, and genetic data derived from studies of these factors. Methods: A search on the Medline, Scielo, and ISI databases was performed using the keyword BPSD for articles published within the last five years. Selected publications were favored, so this review should not be regarded as a systematic study on the subject. Results: The main factors and syndromes comprising BPSD were identified, namely psychosis, depression, and activity. Different ways of clustering symptoms were considered. The main manifestations of psychosis, apathy and depression were focused, relating phenomenology to neuroimaging and pharmacological issues. Conclusions: BPSD is a heterogeneous array of symptoms which can be better understood as clusters. At least three factors can be separated in BSPD, namely psychosis, depression, and activity. This division may offer guidance to clinicians regarding treatment management and follow up of the chosen therapeutic strategy. Resumo Os Sintomas Psicológicos e do Comportamento na Demência (SPCD) são uma característica importante das demências. Entretanto, essa definição congrega uma ampla gama de sintomas e síndromes. Essa é uma fonte de problemas no que tange o melhor conhecimento do comportamento dos pacientes e daí o desenvolvimento de estratégias para aliviar esses sintomas. Objetivos: Essa revisão objetiva descrever os principais fatores e síndromes que compõem os SPCD, além de alguns dados de neuroimagem, psicofarmacológicos e genéticos derivados do estudo desses fatores. Métodos: Foi realizada busca nos bancos de dados Medline, Scielo e ISI utilizando a palavra chave BPSD (SPCD) compreendendo os cinco últimos anos. Foram privilegiadas publicações selecionadas, de modo que a presente revisão não deve ser vista como do tipo sistemática sobre o assunto. Resultados: Os principais fatores e síndromes que compõem os SPCD foram identificados, compreendendo psicose, depresão e atividade. São consideradas diferentes maneiras de se conglomerar os sintomas. As manifestações principais, psicose, apatia e depressão são focalizados, relacionando a fenomenologia à aspectos de neuroimagem e farmacológicos. Conclusões: Os SPCD constituem um conjunto heterogêneo de sintomas que podem ser melhor compreendidos como conglomerados. Ao menos três fatores podem ser separados nos SPCD, psicose, depressão e atividade. Essa divisão pode oferecer uma melhor orientação para o clínico visando o tratamento e o seguimento da resposta a uma determinada estratégia terapêutica escolhida.